Implementasi Model Pembelajaran Quantum Learning pada Mata Pelajaran Akidah Akhlak - Siti Aminah; Syafri Martabe Rizka Nasution (An-Nuha, 2025)
This study aims to describe the implementation of the Quantum Learning model in the Akidah Akhlak subject at MTsN 2 Mandailing Natal. The primary issue examined is how the application of this model enhances the effectiveness of the teaching and learning process. This study employs a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The results indicate that the implementation of Quantum Learning is carried out systematically through several stages: (1) fostering student interest by linking the material to real-life experiences; (2) deepening concepts through interactive discussions; (3) expressing understanding through presentations and projects; (4) reinforcing concepts through repetition; and (5) providing appreciation as a form of celebrating learning success. The application of this model is proven to create an active, enjoyable, and meaningful learning atmosphere, while contributing positively to increasing students' motivation and learning outcomes in Akidah Akhlak at MTsN 2 Mandailing Natal.